CACAT DAN PRESTASI MELALUI PENGALAMAN KOMUNIKASI ATLET PENYANDANG CACAT - Hanny Hafiar (Indonesian Journal of Dialectics, 2012)
The objectives of this dissertation entitled Disabilities and Achievement through the Communication Experiences of Disabled Athletes were to understand the meaning of disabilities, the status as excelled athletes, and the communication experience from the perspective of those excelled disabled athletes. The interpretation also derived from the meaning construction process which involved the interaction between those athletes and the surrounding neighborhood.             This research used qualitative approach with the constructivism paradigm and phenomenological form of study. The subjects were excelled athletes with disabilities which were purposively selected. Data were collected through in depth interviews, participative observations, and literature studies.            The results of this research revealed that the interpretation about disabilities which was acquired by excelled disabled athletes was developed by their awareness, emotions and treatments they received. These factors were then constructed as a set of experience. The set led them to find their own terms which became their particular preferences. Meanwhile, the meaning of their status as excelled athletes was developed through some motives, efforts, follow up actions and interactions with some people who were regarded to have significant roles in their achievement, and also treatments they received after they became so-called excelled athletes with disabilities.            Excelled athletes with disabilities interpreted their unique condition from the perspective of terminology, characteristics, effects, advantages, and positive consequences they have from the disabilities. The status itself was regarded as a social identity which distinguished them from the other disabled people. It brought them became individuals who gained more respects and regarded as people with a better quality of life which could be taken as significant raw models. Furthermore, the communication experiences between the athletes and their neighborhood were influenced by their positive and negative experience while communicating each other, and were also resulted from the interactions with relatives, institutions, and people within the society where they mostly live.